Effect of floor on welfare of lactating cows in small farms of Sirajgonj district, Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
Animal welfare is a relatively new topic and there is a dearth of the report regarding the welfare assessment of dairy cattle in Bangladesh. Therefore, the present study was carried out to assess the effect of floor surface of the dairy sheds on mastitis, skin lesions, cleanliness of body and lameness of lactating cow in smallholders’ production system. To conduct this study, 5 soil type floor, 5 brick paved and 5 concrete floors of small holder dairy units were selected in Sirajgonj district. From each shed, 5 numbers of dairy cows were selected preferably in the first lactation stage. A total 75 milk samples from three different types of the shed were tested for subclinical mastitis using a California mastitis test. The results showed that 40%, 28%, and 32% cows were CMT positive for subclinical mastitis in soil, brick made and concrete type floor, respectively. The prevalence of SCM was not significantly differences among the different types of floor (P>0.05). Cleanliness and hygienic status of the muddy soil type floor were found to be significantly poor in comparison to that of brick made and concrete type floor of dairy farms. The prevalence of skin lesions in different body parts was higher in brick made (62%) and concrete floor sheds (88%) compared to soil bedded (31%) floor. Hair loses in the concrete and brick made floor was significantly higher (P≤0.01) in comparison with the muddy soil floor. The overall prevalence of lameness of the brick made (72%) and concrete type floor was higher (65%) than that of soil bedded shed (48%). There was a significant difference of lameness between soil type and brick made floor of the shed (P>0.05). The study recommends that in order to reduce the high prevalence of subclinical mastitis, skin lesions and lameness in smallholder farmers require to improve floor conditions through regular cleaning of the floor or upgrade to the concrete floor using rubber mat.Res. Agric., Livest. Fish.7(1): 87-95, April 2020